100 Jahre globale Wasserbilanz von Eduard Brückner. Eine Würdigung aus heutiger Sicht - Jaeger, Lutz; Hupfer, Peter; Kessler, Albrecht (ERDKUNDE, 2006)
After paying tribute to the pioneering study of EDUARD BRÜCKNER on the total water balance of the planet earth, including its components, published in 1905, we give a short account of its further development up to now. Estimates of the quantities of water in the different reservoirs still show considerable uncertainities, as does the calculation of the components of the water balance. We present in detail the close relation between the temporal and areal distribution of the terms of the water balance and the elements of the heat balance of the globe. The conclusion of the study consists of a short discussion of the marine water balance and its importance, and the problematics of changes in the global water balance related to climate change.